EFFECT OF GRC AND INTELLECTUAL CAPITAL ON COMPANY PERFORMANCE - Suud Al Habsyi; Harry Suharman; Sofik Handoyo (JRAK, 2021)
This research was conducted on companies that won the Top GRC Award in 2019 and 2020 with secondary data collection methods. The data is collected through purposive sampling techniques. The sample used in this research is 30 companies.The analysis method used is to use SPSS for multiple linear regression analysis. The results present that governance, risk, compliance (GRC) and intellectual capital have a positive effect on the companies performence that have won Top GRC awards.